2023
DOI: 10.1155/2023/9967591
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in Pyridine Scaffold: Focus on Chemistry, Synthesis, and Antibacterial Activities

Abstract: Multidrug-resistant (MDR) pathogens have created a fatal problem for human health and antimicrobial treatment. Among the currently available antibiotics, many are inactive against MDR pathogens. In this context, heterocyclic compounds/drugs play a vital role. Thus, it is very much essential to explore new research to combat the issue. Of the available nitrogen-bearing heterocyclic compounds/drugs, pyridine derivatives are of special interest due to their solubility. Encouragingly, some of the newly synthesized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(7 citation statements)
references
References 74 publications
0
7
0
Order By: Relevance
“…Pyridine and its derivatives play vital roles and are the most extensively applied scaffolds for drug design and synthesis [54]. Several forms of pyridine were shown, along with their biological properties, including antiviral, antimicrobial, and anticancer properties [55][56][57]. El Naggar et al reported that pyridine-ureas showed antiproliferative activity against the MCF-7 cell line with a low IC 50 value [58].…”
Section: Discussionmentioning
confidence: 99%
“…Pyridine and its derivatives play vital roles and are the most extensively applied scaffolds for drug design and synthesis [54]. Several forms of pyridine were shown, along with their biological properties, including antiviral, antimicrobial, and anticancer properties [55][56][57]. El Naggar et al reported that pyridine-ureas showed antiproliferative activity against the MCF-7 cell line with a low IC 50 value [58].…”
Section: Discussionmentioning
confidence: 99%
“…Pyridine moiety is a common and significant heterocyclic modulation, playing an important role in various fields of medicinal chemistry. Pyridine scaffold-containing compounds are commonly of significant interest due to various biological activities such as antimicrobial activities [56]. Such derivatives, in further evaluations against Leishmania strains, can be used to lead different strategies in a Hit-to-Lead process.…”
Section: Antileishmanial Amidoximes Exploring the Pyridine Effect Usi...mentioning
confidence: 99%
“…[19] Among the most prevalent heterocyclic compounds, functionalized pyridines have a lot of applications as agricultural chemicals like insecticides, herbicides, surfactants, [20] chemo sensors, photosensitizers, [21] ligands for catalysis, [22] and therapeutic drugs. [23] Pyrrolopyridines [24] are very important hybrid heterocyclic scaffolds with two significant pharmacophores present in their structure. They exhibit cytotoxic, [25] met kinase inhibitory, [26] antibacterial, [27] JAK-1 selective inhibitory, [28] anticancer [29] and antifungal [30] activities.…”
Section: Introductionmentioning
confidence: 99%